Lincoln's Autocrat : The Life of Edwin Stanton - Marvel, William (Book collections on Project MUSE., 2015)
Edwin M. Stanton (1814-1869), one of the nineteenth century's most impressive legal and political minds, wielded enormous influence and power as Lincoln's Secretary of War during most of the Civil War and under Johnson during the early years of Reconstruction. William Marvel offers a detailed reexamination of Stanton's life, career, and legacy.